Interfaces saúde e educação: a parceria do curso de medicina da Unicid e a prefeitura de Mairiporã - Ferreira, Mônica Izabel (2009)
This research, of qualitative nature, analyzes the impact caused in the students, patients and community by partnership between the Medicine’s course of the UNICID - University City of São Paulo - and the Municipal City hall of Mairiporã. And methodological procedures contemplated the presentation historical of the medical education, in Brazil and the world, bibliographical revision of concepts, like health and partnership, and documental analysis, like the Curricular Lines of direction, Public Politics of Health, philosophy and action of the Only System of Health - SUS - and the Program of Integration in Health in the Community - PISCO -, interviews with the responsible and idealizers for the partnership; questionnaires answered for the students of Medicine and Team of the Family’s health. The results of the research indicate that the partnership school and teams of health contributes for the improvement of the attendance, access of bigger number of people to the medical services, participation of the family and the community in the cares to the sick person, experience and joint of the practical theory and of the curricular contents for the medical future. So, The PISCO, with its objective to insert, already since the first year of the course, the student in the practical of medicine, contributes so that the future practices medicine can apply its knowledge, to evaluate the validity and adequacy of the curriculum, to consider alterations, to know the necessities to the community, to test its option for the medicine and to feel itself useful to the way receives that it as trainee.